Analisis Kemampuan Guru Kelas Tiga dalam Menggunakan Media Gambar pada Pembelajaran IPA di SDN 1 Tembeng Putik - Hadiyaturrido Hadiyaturrido; Nyoman Dantes; Desak Putu Parmiti (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the ability of third-grade teachers to utilize visual image media in Natural Science (Science) instruction at SDN 1 Tembeng Putik during the 2024/2025 academic year. The study employed a qualitative approach using a descriptive method. Data collection techniques included observation, interviews, and documentation. The findings reveal that at the planning stage, teachers had not optimally and systematically incorporated the use of visual image media into the lesson plans. At the implementation stage, visual image media were used fairly frequently; however, classroom interaction was still predominantly teacher-centered through lecture-based methods with limited discussion. At the evaluation stage, visual image media had not yet been integrated into the development of assessment instruments. Factors influencing teachers’ ability to use visual image media include teacher motivation, teaching experience, and understanding of instructional media (internal factors), as well as the availability of facilities, school support, and professional training (external factors). This study recommends strengthening professional development related to instructional media use and enhancing school support to optimize the utilization of visual image media in Science learning.